LESSON THAT CAME TOO LATE: („The meaning“ and „justification“ of suicide in the short story „Krotka“ by F. M. Dostoyevsky) (Heritage, 2024)
The relationship of F. M. Dostoevsky towards suicide is related to the deepest moral questions of humanity. In his diary notes and texts inspired by various news stories about suicides („Two Suicides“, „The Verdict“, „Lesson that Came too Late“ and „Assertions Without Evidence“), he expressed an authentic attitude towards the tragic phenomenon of suicide. Starting from these texts of his, the paper interprets the motive of suicide in the „fantastic story“ „Krotka“ primarily in the context of the Christian idea of ​​the immortality of the soul. Dostoevsky's attitude towards this tragic and, in the Christian understanding, contradictory act, is somewhat heretical. Distinguishing two types of suicide: the one for purely „material“ reasons (motivated above all by the „absence of faith in the immortality of the soul“) and the other, „meek“, „justified“ (for which he directly condemns the abuser of the victim), the writer in connection with the latter indirectly also questions the responsibility of God and calls into question the possibility of fully fulfilling the commandment: „Love one another as yourself“. Dostoevsky takes the side of the meek and raises his voice against abusers, but also his voice goes against God who „willed it that way“.Apart from that, Dostoyevsky's note on the death of his first wife, Maria Dmitrievna (Masha) dated April 16, 1864, is indispensable in the interpretation of the short story „Krotka“, in which he expressed for the first time doubts about the possibility of fulfilling that „goal“, i.e. God's command , because the „law of personality“ interferes with it, „I restrains“. But, regardless of that, Dostoevsky sets this commandment as the supreme goal of man's earthly existence to which he should strive. In this context, the short story „Krotka“ and the „meaning“ of the young woman's suicide, which turns out to be her only way of salvation, should be read.
Keywords: F. M. Dostoyevsky, Krotka, suicide, icon, soul, Lamb of God